A study on factors that influence the resistance to change among employees in Syarikat Air Melaka Berhad (SAMB) / Saidatul Faranadzirah Roslan and Siti Syuhadah Md Johar - Roslan, Saidatul Faranadzirah; Md Johar, Siti Syuhadah (2014)
The purpose of this study is to investigate the relationship between communications and trust with the employees’ resistance to change. The objectives of this study is to determine the relationship between communication with resistance to change among employees, to determine the relationship between employee’s trust toward organization with resistance to change, to identify the factor that influences most on resistance to change, and to give recommendation to the management of SAMB regarding the resistance employees. This study was used questionnaire as instrument to gain the data. The questionnaire is personally administered distribute to 100 respondents which employees who work in Syarikat Air Melaka Berhad (SAMB). The respondent are from eight department in Syarikat Air Melaka Berhad (SAMB) which is human resources, finance, legal, planning, corporate, business development, operation, and business compliance. Pearson correlation is to find out the relationship between communications and trust towards management with the resistance to change. Multiple regressions are applied to find out the most influencing factors of employees resistance to change. The study was found that there are a positive relationship between communications and trust with the employees’ resistance to change. The study was also found that the most factors that influences employees’ resistance to change is communications.